Positioning Destinasi Wisata di Bali Perspektif Solo Traveller - Kadek Melinda Putri; Luh Yusni Wiarti; Hanugerah Kristiono Liestiandre (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This research aims to analyze the positioning of tourism destinations in Bali from the perspective of solo travellers. The rising trend of independent travel highlights the need to understand how solo tourists perceive and select destinations. A quantitative approach was employed by distributing questionnaires to 326 respondents who had experienced solo travel and were familiar with nine global destinations, including Bali. Data analysis techniques used were Multidimensional Scaling (MDS) and Correspondence Analysis (CA). The results indicate that Bali holds a unique and strong position compared to other destinations such as Seoul, Bangkok, and Melbourne. Bali excels in attributes such as comfort, tourist attractions, safety, accessibility, and cultural engagement. Additionally, Bali shares positioning similarities with Reykjavik, particularly in terms of sustainable tourism practices. This study concludes that Bali is a competitive and attractive destination for solo travellers seeking a balance of relaxation, culture, and nature. The findings are expected to serve as a foundation for developing more effective and sustainable destination positioning strategies in the future.